Analysis of KRAS Mutations of Exon 2 Codons 12 and 13 by SNaPshot Analysis in Comparison to Common DNA Sequencing - Rica Zinsky; Servet Bölükbas; Holger Bartsch; Joachim Schirren; Annette Fisseler-Eckhoff (Gastroenterology Research and Practice)
Due to the call for fast KRAS mutation status analysis for treatment of patients with monoclonal antibodies for metastatic colorectal cancer, sensitive, economic, and easily feasible methods are required. Under this aspect, the sensitivity and specificity of the SNaPshot analysis in comparison to the commonly used DNA sequencing was checked. We examined KRAS mutations in exon 2 codons 12 and 13 with DNA sequencing and SNaPshot analysis in 100 formalin-fixed paraffin-embedded tumor tissue samples of pancreatic carcinoma, colorectal carcinoma, and nonsmall cell lung cancer specimens of the primary tumor or metastases. 40% of these samples demonstrated mutated KRAS genes using sequencing and SNaPshot-analysis; additional five samples (45/100) were identified only with the SNaPshot. KRAS mutation detection is feasible with the reliable SNaPshot analysis method. The more frequent mutation detection by the SNaPshot analysis shows that this method has a high probability of accuracy in the detection of KRAS mutations compared to sequencing.